Pengaruh Etos Kerja Islam Terhadap Komitmen Kerja Karyawan Yayasan Pondok Pesantren Hidayatullah Surabaya - Novandi Arif Pratama; Ari Prasetyo (Universitas Airlangga, 2014)
This research was aimed to investigate the effect of Islamic work ethics to the organizational commitment on Yayasan Pondok Pesantren Hidayatullah in Surabaya. This study used questionnaires in primary data collection and quantitative approaches. Experiments were done using simple linear regression, where the dependent variable (Y) is the organizational commitment and the independent variable (X) is Islamic work ethics. The research sample were taken by nonprobability sampling with purposive sampling method. The research sample was 58 employees work in Yayasan Pondok Pesantren Hidayatullah Surabaya.Based on the findings, it obtained simple linear regression equation : Y = 5,908+0,452X. The magnitude of the influence of Islamic work ethics to the organizational commitment on Yayasan Pondok Pesantren Hidayatullah Surabaya. According to the final summaries of description data analysis from Islamic work ethic variable, that is have a resolute stand and got no effect (X1.3) has the lowest mean value, Yayasan Pondok Pesantren Hidayatullah be expected to capable of keeping and increasing the human resources, in shaping employees resolute and not easily influenced, so as toimprove the islamic work ethic. For the next research can be done with distinguish the permanent employees and not-permanent employees which later result from the study willbe compared to find out the influence of Islamic work ethic to deeper Organizational Commitment. REFERENCESAhmad Janan Asifudin, 2004, Etos Kerja Islami, Muhammadiyah University Press, Surakarta.Akbar, Toriqul Hajjil. 2013. Pengaruh Gaya Kepemimpinan Islam Tehadap Komitmen Kerja Dan Pengaruhnya Terhadap Kepuasan Kerja Karyawan Pada Bank BNI Syariah Surabaya. Skripsi S1. Surabaya: Unair.Alex S Nitisemito. 2001. Manajemen Personalia.Edisi kedua. Ghalia Indonesia.Ali, J.A. and Al-Owaihan, A. 2008. ”Islamic work ethic: a critical review” Cross Cultural Management an International Journal. Vol. 15 No. 1.Anshori, Muslich dan Sri Iswati. 2009. Metodologi Penelitiian Kuantitatif. Surabaya: Airlangga University Press.Greenberg, J. 2002. Behavior In Organization. Seventh Edition. New Jersey: Prentice Hall.Hayati, Keumala. 2012. Islamic Work Ethic: The Role of Intrinsic Motivation, Job Satisfaction, Organizational Commitment and JobPerformance. Procedia - Social and Behavioral Sciences 65 ( 2012 ) 272 – 277.Indica, I Wayan Marsalia. 2013. Pengaruh Etos Kerja Islami dan Gaya Kepemimpinan Transformasional Terhadap Komitmen Organisasional dan Kinerja Karyawan.Mangkunegara, Anwar Prabu. (2005). Perencanaan dan Pengembangan Sumberdaya Manusia. Bandung: PT. Refika Aditama.Manullang, M. (2005) Dasar-dasar Manajemen. Yogyakarta : Gadjah Mada University Press.Moelyadi , Naghmeh Nancy. 2009. Islamic Work Ethic And Muslim Religious Beliefs Impact On Organizational Commitment In The Workplace.Poerwanti, E.S., Margono Setiawan & Bambang Swasto. 2002. Pengaruh Kopensasi Terhadap Kerja dan Dampaknya pada Komitmen Karyawan pada Komitmen karyawan (Study pada PT Telekomunikasi Tbk. Kandatel Malang). Jurnal Ekonomi dan Bisnis. Vol. XXII, No.1. Hal 59-71.Robbins, P Stephen, Handyana Pujaatmaka (Penterjemah). 2001. Perilaku Organisasi, Konsep, Kontroversi, Aplikasi, Jakarta : PT. Prenhallindo.Robbins SP, dan Judge. 2007. Perilaku Organisasi, Salemba Empat, Jakarta.Sinamo, Jansen. 2005. Delapan Etos Kerja Profesional; Navigator Anda Menuju Sukses. Bogor: Grafika Mardi Yuana.Sopiah. 2008. Perilaku Organisasional. Yogyakarta : C.V Andi Offset.Sugiyono. 2010. Metode Penelitian Bisnis: Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Yamin, Sofyan & Kurniawan, Heri. 2009. SPPS Complete. Jakarta: Salemba Infotek